Lindhe's clinical periodontology and implant dentistry - Berglundh, Tord, 1954-; Giannobile, William V.; Lang, Niklaus Peter; Sanz, Mariano (Professor) (Hoboken : John Wiley & Sons, Inc., 2022)
'Discover the latest edition of the cornerstone reference on periodontology and implant dentistry that combines scholarship and science with practical clinical instruction The Seventh Edition of Lindhe's Clinical Periodontology and Implant Dentistry brings together a distinguished team of periodontal specialists and academics who deliver another must-have resource for students, researchers, and practitioners specializing in periodontal care and implant dentistry. Seamlessly integrating the foundational science behind periodontology with practical clinical protocols in two comprehensive volumes, the chapters cover anatomy, microbiology, occlusion trauma, pathology, tissue regeneration, treatment planning protocols, infection control, reconstructive therapy, occlusal and prosthetic therapy, and more. The Seventh Edition of Lindhe's Clinical Periodontology and Implant Dentistry: Provides an introduction to anatomy, including periodontal tissues, the edentulous ridge, the mucosa at teeth and implants, and osseointegration Discusses the epidemiology of periodontal and peri-implant diseases Explores the microbiology, including dental biofilms and calculus, periodontal infections, peri-implant infections, the pathogenesis of gingivitis and periodontitis, and the genetic susceptibility to periodontal disease. Includes the latest perio- and peri-implant disease classifications Contains updated evidence-based preventive and treatment modalities for the treatment of periodontal and peri-implant diseases Features the latest evidence-based therapeutic alternatives on the use of dental implants to rehabilitate the lost dentition Perfect for postgraduate dental students, researchers, and practitioners specializing in periodontal care and implant dentistry, Lindhe's Clinical Periodontology and Implant Dentistry continues to be the cornerstone reference work on periodontology'--
Preceded by Clinical periodontology and implant dentistry / edited by Jan Lindhe and Niklaus P. Lang ; associate editors, Tord Berglundh, William V. Giannobile, Mariano Sanz. 6th edition. 2015.
Keywords: Periodontal Diseases; Dental Implantation; Dental Implants